“THE INFLUENCE OF PREVIOUS AUDIT OPINION AND FINANCIAL CONDITION ON GOING CONCERN AUDIT OPINION (EMPIRICAL STUDY OF PROPERTY AND REAL ESTATE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE FOR PERIOD 2012 TO 2014)” - Mutiara Nurul Abdau (Jurnal Ilmiah Mahasiswa FEB, 2015)
Prior to this study, there are several previous researches that examine the factors that influence the granting of going concern audit opinion. However, the results of these studies are still generating inconsistencies. Therefore this research was made to reexamine some of the factors that indicated may affect the granting of going concern audit opinion. This study used secondary data, which is Property and Real Estate Company listed on the Indonesian stock exchange for period 2012 to2014. Population used in this research is 49 companies taken from IDX and then through the purposive sampling process, 19 companies are elected to be sample. Logistic regression analysis is used as the technique to test the hypothesis. Results of hypothesis testing concluded that the audit opinion the previous year and the leverage ratio are proven to positively influence the going concern audit opinion. While the liquidity ratio has significant negative influence on going concern audit opinion. However, this study cannot prove that profitability ratio possessed has significant influence on the granting of going concern audit opinion.Keywords: audit, going concern audit opinion, financial ratio, previous year audit opinion, and logistic regression